Reflections on Argentina immigration policy and regional integration - Nicolao, Julieta (Revista Tribuna Internacional, 2013)
The aim of this article is to reect on the place that has been given to regional integration, and specifically to MERCOSUR, in Argentina’s immigration policy since the enactment of the Immigration Act 25.871/2004. &e paper addresses political and social debate prior to the enactment of the rule, the most important de%nitions which enshrines the text of the law regarding the regulation of immigration from MERCOSUR countries, and the role that Argentina has recently been playing under the South American dialogue on the subject.